Effects of alterations in dietary carbohydrate intake on running performance during a 10 km treadmill time trial - Pitsiladis, Y. P.; Duignan, C.; Maughan, R. J. (British Journal of Sports Medicine, 1996)
OBJECTIVE: To examine the influence of a seven day diet manipulation on performance during a 10 km treadmill time trial in trained runners. METHODS: Six trained runners ran two 10 km time trials on a treadmill set at a constant 4% gradient, each after a 7 d period of dietary manipulation. The two experimental diets were a low carbohydrate (CHO) diet (40% CHO by total energy) to be consumed for 7 d, and a high CHO diet containing 55% CHO for the first 4 d followed by 70% CHO for the remaining 3 d. Blood samples were obtained before and immediately after each run. Expired gases were collected and heart rate monitored. RESULTS: Performance time following the high CHO [48.6(SD 2.7) min] and low CHO [48.6(2.3) min] diets was not different (P = 0.72), nor were there any differences in running speed between conditions. No significant differences were found between conditions in any of the metabolites measured (blood lactate, glucose, glycerol, and plasma free fatty acids). The rate of CHO oxidation was greater on the high CHO diet compared to the low CHO diet (P < 0.05). Heart rate was not different between conditions. CONCLUSIONS: The results of this study indicate that moderate changes in the composition of the diet do not affect 10 km running performance in trained subjects.